Cortical Microinfarcts Detected by 3-Tesla Magnetic Resonance Imaging: Differentiation Between Cerebral Amyloid Angiopathy and Embolism. Issue 3 (March 2020) - Ishikawa, Hidehiro; Ii, Yuichiro; Shindo, Akihiro; Tabei, Ken-ichi; Umino, Maki; Ito, Ai Ogawa; Matsuura, Keita; Taniguchi, Akira; Matsuyama, Hirofumi; Niwa, Atsushi; Ogura, Toru; Yoshimaru, Kimiko; et al.
Abstract : Background and Purpose—: Cortical microinfarcts (CMIs) are small ischemic lesions found in cerebral amyloid angiopathy (CAA) and embolic stroke. This study aimed to differentiate CMIs caused by CAA from those caused by microembolisms, using 3-Tesla magnetic resonance imaging. Methods—: We retrospectively investigated 70 patients with at least 1 cortical infarct <10 mm on 3-dimensional double inversion recovery imaging. Of the 70 patients, 43 had an embolic stroke history (Emboli-G) while 27 had CAA-group. We compared the size, number, location, and distribution of CMIs between groups and designed a radiological score for differentiation based on the comparisons. Results—: CAA-group showed significantly more lesions <5 mm, which were restricted to the cortex ( P <0.01). Cortical lesion number was significantly higher in Emboli-G than in CAA-group (4 versus 2; P <0.01). Lesions in CAA-group and Emboli-G were disproportionately located in the occipital lobe ( P <0.01) and frontal or parietal lobe ( P =0.04), respectively. In radiological scoring, ≥3 points strongly predicted microembolism (sensitivity, 63%; specificity, 92%) or CAA (sensitivity, 63%; specificity, 91%). The areas under the receiver operating characteristic curve were 0.85 and 0.87 for microembolism and CAA, respectively. Conclusions—: Characteristics of CMIs on 3T-magnetic resonance imaging may differentiate CMIs due to CAA from those due to microembolisms. Abstract : Supplemental Digital Content is available in the text.